1999
DOI: 10.1002/(sici)1521-401x(199912)27:6<409::aid-aheh409>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Fulvic Acid Fractions of a Contaminated Groundwater

Abstract: Two fulvic acid (FA) samples taken from a former gas production facility in the Southwest of Germany were characterized using advanced fluorescence techniques. Steady‐state fluorescence (fluorescence excitation, synchronous fluorescence) as well as time‐resolved fluorescence were applied. Distinct differences between the sample B22 FA taken within the contamination plume and the sample B53 FA taken downstream were found. Comparison with a model compound for metabolites and humic substances revealed that due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…On the basis of the retention times in SEC and HIC compared to a standard the peak can be tentatively attributed to salicylic acid. The tentative identification could be confirmed by further investigations applying synchronous fluorescence spectroscopy [16]. Since, it is obvious that the peak is only reduced in size by solvent extraction at neutral pH and salicylic acid should be associated with the FA by weak intermolecular forces, too.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…On the basis of the retention times in SEC and HIC compared to a standard the peak can be tentatively attributed to salicylic acid. The tentative identification could be confirmed by further investigations applying synchronous fluorescence spectroscopy [16]. Since, it is obvious that the peak is only reduced in size by solvent extraction at neutral pH and salicylic acid should be associated with the FA by weak intermolecular forces, too.…”
Section: Resultsmentioning
confidence: 70%
“…Synchronous and time-resolved fluorescence measurements are promising approaches to further investigate these interactions and to confirm these results and interpret the fluorescing compounds. Results will be given in another paper [16].…”
Section: Discussionmentioning
confidence: 99%
“…These two lifetimes indicate the existence of a short and a long-living fluorescence species contributing to the HA fluorescence. The obtained lifetimes have the same order of magnitude as those reported by Kumke et al for aqueous solutions of fulvic acid [30] and natural organic matter [31]. There, the authors reported further the occurrence of a third fluorescence contribution with a longer fluorescence lifetime τ 3 in the range from 11 to 24 ns.…”
Section: Results Of Fs-trlfs Measurementsmentioning
confidence: 99%
“…These natural compounds with unordered molecular structures represent an organic pool, that is objective of numerous investigations especially with respect to structure analysis (e.g. Thurman and Malcolm 1983;Sonnenberg et al 1989;Schulten and Leineweber 1996;Göbbels and Püttmann 1997;Kumke et al 1999;Esteves and Duarte 2000) or the interaction with natural occurring or anthropogenic low molecular weight substances (e.g Huber et al 1992;Jensen-Korte et al 1987;Klaus et al 1998a/b;Zwiener et al 1999, Northcot and.…”
Section: Natural Compoundsmentioning
confidence: 99%